A Thousand Dissonances: Music Research and the Nomadic Female Composer. - Macarthur, Sally (Australian Feminist Studies, 2009)
This article discusses the influence of feminism to music research. It states that feminism in musicology has given rise to new form of positivism. It assesses how a composer's subjectivity is formed through music and determines whether it can be viewed as a virtual force of feminine difference, and sets the Australian composer Anne Boyd as an example. It discusses the discourses of music theory and musicology and the dissonances in music research. The concept of activist nomad in musicology is also assessed.